COMPRESSIVE BEHAVIOR OF SOIL AS AFFECTED BY AGGREGATE SIZE WITH DIFFERENT TEXTURES IN TURKEY - K. Barik M. Y. Canbolat R. Yanık; K. Rafiq Islam (Journal of Animal and Plant Sciences, 2011)
Soil compactability is affected by aggregate size distribution of soil. The objective of this study was to determine the effects of aggregate size on compressive behaviour of soils with different textures. The study was conducted on surface soil samples (0-20 cm) of; coarse textured (TC) and fine textured (TF) soils. Aggregates were separated into three different aggregate size groups (4.0-2.0 mm; 2.0-0.84 mm and <0.84 mm) by dry sieving. The dry bulk density and saturated hydraulic conductivity of the TC and TF soils for each aggregate size group was also determined under three different compaction efforts (0, 45, 90 KPa) for saturated condition of soil water content. The maximum dry bulk density values of aggregate size groups of the TC soil were significantly higher than those of the TF soil, but the optimum water content values of the TF soil were significantly higher than those of the TC soil. The dry bulk density and saturated hydraulic conductivity values of the TC soil were significantly higher than those of the TF soil. The results of this study clearly indicated that the compressive behaviour of aggregate size on soil compactibility with wide variation in soil dry bulk is mainly affected by soil texture and water content.
Keywords: Aggregate size; soil compaction; bulk density; hydraulic conductivity